The role of selected polymorphisms of receptor proteins in the pathogenesis of type 2 diabetes, prediabetic quantitative traits and obesity in a Polish population - Frey, Jakub (2007)
462 unrelated individuals with type 2 diabetes mellitus and 428 healthy volunteers answered a questionnaire, regarding in the diabetes group: age of onset of the disease, its treatment, chronic complications, in both groups: other diseases, use of medication, smoking status, familial history of type 2 diabetes and other medical issues. In all subjects blood was drawn for biochemical and genetic testing. In 305 individuals with normal fasting glycemia an oral glucose tolerance test was performed – those with abnormal glucose tolerance were excluded from further analysis. In all study subjects the genotypes of polymorphisms: Gly168Ser i Phe260Leu in GLP1R gene and Pro12Ala in the PPARγ gene were ascertained. Moreover in individuals from both groups with the BMI >=25 a mutation Pro115Gln in PPARγ was genotyped. Polymorphism Gly168Ser in GLP1R was significantly more frequent among type 2 diabetics (p=0,027 for an additive effect of mutated allele). Stratification analysis showed the relation as being dependent on association present in women p=0,012). In order to investigate the effect of above-mentioned genetic polymorphisms on prediabetic phenotypes in the group of patients with normal glucose tolerance verified in OGTT an analysis of their association with fasting and 120 minutes post-glucose glycemia and insulnemia and insulin sensitivity and secretion indices derived from thos
Keywords: GLP1; polymorphism; type 2 diabetes; PPARgamma; gene